Analisis Profitabilitas Bank BUMN Indonesia Tahun 2013 - 2023 - Musadat, Irfan Achmad; Aprianti, Vika; Sofyan, Mohammad (Ma'soem University, 2025)
Banking serves as an intermediary institution that supports the economy through financing for consumption and production. Post-Covid-19, banks have assisted businesses through credit restructuring and new loan disbursements but face challenges in maintaining credit quality and preventing NPL increases amid the global economic slowdown. Investment, which is expected to drive economic growth, remains limited. Bank Mandiri, BRI, BNI, and BTN play strategic roles with different focuses: Mandiri on corporate and retail financing, BRI in the micro and SME sectors, BNI with a strong international network, and BTN in housing finance. Each bank implements specific strategies to maintain credit quality and profitability. Indonesia’s economic growth has fluctuated over the past decade, with a sharp decline in 2020 due to the pandemic, followed by moderate recovery in 2021-2022. Bank profitability, measured by ROA, is a key indicator of financial performance. This study employs a descriptive method to analyze profitability ratios, enabling a comprehensive evaluation of factors such as credit restructuring, growth strategies, and risk management. This analysis provides insights into profitability trends and the challenges banks face in maintaining stability and growth in Indonesia’s financial sector.